Impact of SIRPα polymorphism on transplant outcomes in HLA‐identical living donor kidney transplantation. Issue 9 (11th July 2021) - Garcia‐Sanchez, Cynthia; Casillas‐Abundis, M. Aurora; Pinelli, David F.; Tambur, Anat R.; Hod‐Dvorai, Reut
Abstract: Signal‐regulatory protein α (SIRPα), a polymorphic inhibitory membrane‐bound receptor, and its ligand CD47 have recently been implicated in the modulation of innate immune allorecognition in murine models. Here, we investigate the potential impact of SIRPα donor‐recipient mismatches on graft outcomes in human kidney transplantation. To eliminate the specific role of HLA‐matching in alloresponse, we genotyped the two most common variants of SIRPα in a cohort of 55 HLA‐identical, biologically‐related, donor‐recipient pairs. 69% of pairs were SIRPα identical. No significant differences were found between donor‐recipient SIRPα‐mismatch status and T cell‐mediated rejection/borderline changes (25.8% vs. 25%) or slow graft function (15.8% vs. 17.6%). A trend towards more graft failure (GF) (23.5% vs. 5.3%, P  = .06), interstitial inflammation (50% vs. 23%, P  = .06) and significant changes in peritubular capillaritis ( ptc ) (25% vs. 0%, P  = .02) were observed in the SIRPα‐mismatched group. Unexpectedly, graft‐versus‐host (GVH) SIRPα‐mismatched pairs exhibited higher rates of GF and tubulitis (38% vs. 5%, P  = .031 and .61 ± .88 vs. 0, P  = .019; respectively). Whether the higher prevalence of ptc in SIRPα‐mismatched recipients and the higher rates of GF in GVH SIRPα‐mismatched pairs represent a potential role for SIRPα in linking innate immunity and alloimmune rejection requires further investigation in larger cohorts.